Pengaruh Pembelajaran Kooperatif Tipe Group Investigation dengan Media Berbeda dan Gaya Belajar Terhadap Kemampuan Mengidentifikasi Hasil-Hasil Kebudayaan Masyarakat Indonesia - Siswati, Siswati (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
The purpose of research is to know the different influence in using different media on cooperative learning type Group Investigation in increasing the ability to identify the result of Indonesian society. The kind of research in quasi experiment with posstest only control design consisting of two independent variables, one moderator variable and one independent variable.Independent variable is the usage of picture media and museum model in investigation group learning, moderator variable is active-refletive learning while dependent variable is the ability in indentifying the culture results of Indonesian society. Research population is the whole class of the first yearsstudents both SMAN I Kauman consisting of 328 students and SMAN I Tulungagung consisting of 150 students. The research uses purposive sampling with the approaching class (class X A, class X B) and (class X C , class X D). Class X A and X B as experiment classes 70 student and class X C and X D as controlled classes as 69 students. Experimnet class is taught with GI learning while controlled class uses museum media. Data is collected with learning style test and post test items. The data results are analyzed by using MANOVA statistic with 5% signifikant level. The results of research are (1) there different between the application of learning cooperative, cooperative learning method investigation group type GI with picture media and museum media toward the ability in identifying with the proaf of means of follows media museum (79,53) is higher than picture media (76.21), (2) There different between active and refletive learning style toward the ability identify the culture of Indonesian Society. It’s tested by using MANOVA statistic with signifikant 0,000 < 0,05 it means H0 is refused because of sig. < 0.05. (3) There is interaction between cooperative learning of investigation group type (GI) with picture media and museum media , next learning style toward the ability to identify the culture results of Indonesian society. It’s tested by using MANOVA statistic with signifikant 0,028 < 0,05 it means H0 is refused because of sig. < 0.05. It means there is interaction between media, learning style and the ability to identify.